Retrieval of Separated Endodontic Ni-Ti Rotary File with the Aid of Hypodermic Needle and K-File: A Case Report - S Pallavi; NJ Nagaraj (Journal of Clinical and Diagnostic Research, 2022)
One of the most prevalent operational errors that can occur during endodontic therapy is instrument separation. A fractured instrument may cause a blockage in the root canal, impeding the cleaning and shaping process. There are numerous recommended ways for retrieving a separated instrument, some of which are challenging to implement in clinical practice. Some of these procedures may need removal of substantial root dentin, which may weaken the tooth structure. This case report describes an alternate method for removing a fractured endodontic instrument from the root canal using a hypodermic needle and a K-file. A 31-year-old female patient came to the Department of Conservative Dentistry and Endodontics with the chief complaint of pain in the upper left front tooth region since two weeks. The clinical and radiographic examination indicated the existence of a broken Nickel-Titanium (Ni-Ti) rotary file along the coronal third of the root canal till apex. Under magnification, the fragment was initially exposed by creating a 2 mm trough around the fractured instrument using ultrasonics. In order to fix the fragment, a hypodermic needle was introduced into the root canal and the K-file was fitted in the needle lumen. Together, the fragment was removed without any complications. This technique can be used as a safe, easy, and low-cost approach of fractured instrument retrieval from the root canal.